STATIC STRESS AND DEFORMATION ANALYSIS OF GANESHA PORTABLE ELECTRIC SCOOTER (E-GASPOL) FRAME USING SOLIDWORKS SOFTWARE - Komang Purnayasa; I Gede Wiratmaja; Nyoman Arya Wigraha (Jurnal Pendidikan Teknik Mesin, 2023)
This study aims to determine and minimise static stress and increase the safety factor on the Electric Ganesha Scooter Portable (E-GASPOL) vehicle frame. The type of development research used is the R2D2 type (Reflective,  Recursive, Design and Development). The data analysis technique used is the finite element method, this method can solve static problems. From the data of the static stress analysis results on the four designs, the results of the modified vehicle frame design 3 have the best value, namely obtaining a maximum stress value of 1,255 x N/m conditions without rider load, this result has a decrease of 58.55% from the standard design and with a rider load of 7,699x N/m, this result has a decrease of 58.56% from the standard design. The maximum displacement value was 1,453 x mm in the condition without rider load, this result decreased by 77.718% from the standard design and with rider load it was 8,791 x mm, this result decreased by 78.10% from the standard design. In this study, the smaller the stress and displacement values, the better the frame strength, so it can be concluded that the modified frame is better and stronger than the standard frame.